Characterizing Hippocampal Oscillatory Signatures Underlying Seizures in Temporal Lobe Epilepsy - Mokhothu, Thato Mary; Tanaka, Kazumasa Zen (Frontiers in Behavioral Neuroscience, 2021)
Temporal Lobe Epilepsy (TLE) is a neurological condition characterized by focal brain hyperexcitability, resulting in abnormal neuronal discharge and uncontrollable seizures. The hippocampus, with its inherently highly synchronized firing patterns and relatively high excitability, is prone to epileptic seizures, and it is usually the focus of TLE. Researchers have identified hippocampal high-frequency oscillations (HFOs) as a salient feature in TLE patients and animal models of this disease, arising before or at the onset of the epileptic event. To a certain extent, these pathological HFOs have served as a marker and a potential target for seizure attenuation using electrical or optogenetic interventions. However, many questions remain about whether we can reliably distinguish pathological from non-pathological HFOs and whether they can tell us about the development of the disease. While this is an arduous task to perform in patients, animal models of TLE provide an excellent opportunity to study the characteristics of HFOs in predicting how epilepsy evolves. This minireview will 1) summarize what we know about the oscillatory disruption in TLE, 2) summarize knowledge about oscillatory changes in the latent period and their role in predicting seizures, and 3) propose future studies essential to uncovering potential treatments based on early detection of HFOs.